Histological and immunohistochemical study of estrogen and progesterone receptors in normal human breast tissue in adult age groups vulnerable to malignancy. Issue 6 (29th April 2016) - Goyal, R.; Gupta, T.; Gupta, R.; Aggarwal, A.; Sahni, D.; Singh, G.
Abstract : Analysis of receptor status has become standard procedure for assessing breast cancer patients. Estrogen causes epithelial proliferation in breast tissue via the estrogen receptor (ER). The progesterone receptor (PR) is also regulated by the estrogen gene. Analyzing ER and PR together gives information regarding the likely response of carcinoma patients to hormonal therapy. The aim of the present study was to record the expression patterns of ER and PR in normal mammary tissue in different age groups to provide reference data to facilitate histological diagnosis. Breast tissues from the upper outer quadrant of each side of 27 adult female cadavers were examined after H & E staining. ER and PR were identified and examined by immunohistochemistry. The percentage area occupied by parenchyma relative to stromal tissue was calculated in different age groups and was about 4:6, 3.5:6.5, 3:7, 2:8, and 1.5:8.5 in the 3rd, 4th and 5th, 6th, 7th, 8th and 9th, and 10th decades of life, respectively. Both ER and PR were present in all age groups and the numbers of both receptors were maximal during the 4th decade. The distribution and staining patterns for both ER and PR were recorded in different age groups. The contiguous pattern of ER, which is considered pathognomonic of breast carcinoma, was not seen except in one case in the 6th decade. Moderately stained ER and PR receptor sites predominated throughout. The study of normal breast tissue of similar age might provide comparisons that will help histopathologists to make clinical diagnoses from breast biopsies. Clin. Anat. 29:729–737, 2016. © 2016 Wiley Periodicals, Inc.